2016
DOI: 10.1111/clr.12979
|View full text |Cite
|
Sign up to set email alerts
|

The influence of titanium surface characteristics on macrophage phenotype polarization during osseous healing in type I diabetic rats: a pilot study

Abstract: Diabetic conditions greatly increased the expression of proinflammatory cytokines during osseous healing. The modSLA surface was shown to promote an M2-like macrophage phenotypic response in titanium adherent macrophages despite the significantly elevated inflammatory environment induced by uncontrolled type I diabetes. Modulation of the macrophage phenotype by the modSLA surface in the early healing period was associated with osseous healing under both healthy and uncontrolled diabetic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Therefore, our results indicated that a delayed and prolonged inflammatory response characterised the osseous wound healing events in the diabetic status, which is in accordance with evidence from Lee et al. (), who have shown that experimental T1DM significantly increases the expression of pro‐inflammatory cytokines during the regeneration of calvarial CSDs according to the GBR principle. Furthermore, our observations are in accordance with a recent clinical study demonstrating that pro‐inflammatory cytokines and chemokines were upregulated in T2DM patients with bone fracture, as well as in osteoblasts subjected to high glucose stimulation (Sun et al.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our results indicated that a delayed and prolonged inflammatory response characterised the osseous wound healing events in the diabetic status, which is in accordance with evidence from Lee et al. (), who have shown that experimental T1DM significantly increases the expression of pro‐inflammatory cytokines during the regeneration of calvarial CSDs according to the GBR principle. Furthermore, our observations are in accordance with a recent clinical study demonstrating that pro‐inflammatory cytokines and chemokines were upregulated in T2DM patients with bone fracture, as well as in osteoblasts subjected to high glucose stimulation (Sun et al.…”
Section: Discussionsupporting
confidence: 93%
“…All experiments were carried out in triplicate. Previous studies by our group using the same calvarial defect model to assess the effects of titanium surface characteristics on macrophage phenotype and osseous healing (Lee, Hamlet, & Ivanovski, ) showed this was sufficient to demonstrate statistically significant differences between mean values.…”
Section: Methodsmentioning
confidence: 84%
“…Hydrophobic materials, for example, have been shown to enhance monocyte adhesion (Hezi-Yamit et al, 2009), whereas hydrophilic or neutral surfaces can inhibit macrophage adhesion but enhance the release of pro-inflammatory cytokines and chemokines (Alfarsi et al, 2014;Hamlet et al, 2012;Hotchkiss, Ayad, Hyzy, Boyan, & Olivares-Navarrete, 2017;Hotchkiss et al, 2016;Jones et al, 2007). More recently, a hydrophilic titanium surface with nanotopography (modSLA) has been shown to modulate the early inflammatory response in vivo promoting polarization of macrophages to an M2-like phenotype, even in diabetic conditions where an exaggerated pro-inflammatory environment is a distinguishing feature (Lee et al, 2017). Titanium surface nanotopography has also been shown to regulate both macrophage cell shape (McWhorter, Wang, Nguyen, Chung, & Liu, 2013), the release of cytokines (Luu, Gott, Woo, Rao, & Liu, 2015) and restrict cytoskeletal remodelling-associated signalling by macrophages leading to reduced cell to cell fusion, potentially moderating the foreign body reaction (Padmanabhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that both the hydrophilic and hydrophobic SLA surfaced implants function well and display high survival rates following implantation . Additionally, hydrophilicity of active SLA surfaces improves biocompatibility, which is also responsible for fighting bacterial infection as it promotes downregulation of pro‐inflammatory cytokines and consequently modulates inflammation . However, more knowledge is required to better understand the influence of the implant surface on bone formation under hyperglycemic conditions combined with an inflammatory environment associated with peri‐implantitis.…”
Section: Introductionmentioning
confidence: 99%